On Popular Music: Philip Tagg, William Straw / À propos de musique populaire : Philip Tagg, William Straw - Pedneault, Julie (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2003)
In the course of the last decade, the study of popular music has gradually taken its place as one of the most important branches of musicology. Is Montreal on its way to becoming one of the centres of this institutionalization? William Straw (Director of the Graduate Programme in Communication Studies at McGill) and Philip Tagg (senior professor at the University of Montreal) discuss the current state and future of this discipline. They speak both about the field, its place in the university curriculum, and its most active and promising orientations.